(untitled) (Bangladesh Medical Journal, 2026)
Despite legal restrictions on early marriage, teenage pregnancy remains highly prevalent in Bangladesh and is associated with adverse maternal and neonatal outcomes. Low birth weight (LBW) and preterm birth are major contributors to neonatal morbidity and mortality. This study aimed to determine the proportion of preterm delivery and LBW among teenage mothers and to describe associated sociodemographic and obstetric factors. This cross-sectional study was conducted from June 2021 to March 2024 in the Department of Obstetrics and Gynecology at Dhaka Medical College Hospital. A total of 85 pregnant adolescents aged 16–19 years were enrolled using predefined criteria. Data were collected using a semi-structured questionnaire that covered sociodemographic characteristics, reproductive history, obstetric complications, and neonatal outcomes. Preterm birth was defined as delivery before 37 completed weeks, and LBW as birth weight <2.5 kg. The mean age of participants was 18.38 ± 0.64 years, with more than half aged ≤18 years. The majority resided in rural areas (92.9%), and 41.2% had discontinued formal education, indicating notable socioeconomic vulnerability. Early marriage and low socioeconomic status were common, with the majority belonging to lower-income households and being economically dependent. Oligohydramnios was the most frequent obstetric complication (10.6%), followed by other conditions, including pregnancy-induced hypertension and reduced fetal movements. Live births accounted for 88.2% of outcomes. LBW was observed in 24.0% of neonates, while preterm delivery occurred in 10.7% of cases. Cesarean section was the predominant mode of delivery (62.7%), reflecting the high-risk nature of adolescent pregnancies. Teenage pregnancy in Bangladesh is associated with a considerable burden of adverse neonatal outcomes, particularly LBW and preterm birth, alongside high rates of obstetric complications and cesarean delivery. These findings highlight the need for strengthening adolescent-friendly reproductive health services, improving access to timely and adequate antenatal care, and addressing underlying socioeconomic determinants to reduce risks in this vulnerable population. Bangladesh Med J. 2025 Sept; 54(3): 40-46